Naïve advice in financial decision making: Hidden costs of a free offer - Julia Sprenger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
The current study examines individual decision making in the field of personal finance. A laboratory experiment investigates the way naïve advice influences the decisionmaking process. When advice is offered on demand, participants prefer expert over naïve advice. Although naïve advice is only half the price of expert advice, demand for naïve advice is negligible. When naïve advice is given unsolicited, however, it has nevertheless a strong impact on the decision process by lowering engagement in information acquisition and promoting a passive adoption of the recommended option. While high levels of financial literacy buffer this effect, issuing a warning does not. In case compliance with naïve advice leads to a low decision quality and the saving in information acquisition costs does not make up for this effect, the free offer of naïve advice produces financial losses. This can be interpreted as hidden costs of free naïve advice resulting from a switch in information strategy. People with low financial literacy are most vulnerable to this effect. – – Dieses Papier untersucht individuelles Entscheidungsverhalten im Bereich Finanzen. Ein Experiment beleuchtet auf welche Art naiver Rat den Entscheidungsprozess beeinflusst. Wird Rat nur auf Nachfrage erteilt, so bevorzugen die Teilnehmer den Expertenrat gegenüber dem naiven Rat. Obwohl der naïve Rat nur halb so teuer ist wie der Expertenrat, ist die Nachfrage nach naivem Rat verschwindend gering. Wird naiver Rat jedoch ungefragt erteilt, hat er dennoch einen starken Einfluss auf den Entscheidungsprozess, denn er senkt das Engagement in der Informationsbeschaffung versträkt die passive Ausrichtung an der empfohlenen Option. Ein hohes Niveau an financial literacy reduziert diesen Effekt, eine Warnung vermag dies dagegen nicht. Falls die Befolgung des naiven Rats zu einer geringen Entscheidungsqalität führt und die Einsparung bei den Kosten der Informationbeschaffung diesen Effekt nicht ausgleichen, führt das Gratisangebot des naiven Rats zu finanziellen Verlusten. Dies kann als versteckte Kosten des frei verfügbaren naiven Rats interpretiert werden, die aus einem Wechsel in der Informationsstrategie resultieren. Menschen mit geringer financial literacy sind besonders anfällig für diesen Effekt.
Keywords: C91; G02; D83; 330; Financial literacy; financial decision making; experiment; naïve advice